Photodriven Charge Separation and Transport in Self‐Assembled Zinc Tetrabenzotetraphenylporphyrin and Perylenediimide Charge Conduits1. Issue 13 (19th February 2014) - Roznyatovskiy, Vladimir V.; Carmieli, Raanan; Dyar, Scott M.; Brown, Kristen E.; Wasielewski, Michael R.
Abstract Zinc tetrabenzotetraphenyl porphyrin (ZnTBTPP) covalently attached to four perylenediimide (PDI) acceptors self‐assembles into a π‐stacked, segregated columnar structure, as indicated by small‐ and wide‐angle X‐ray scattering. Photoexcitation of ZnTBTPP rapidly produces a long‐lived electron–hole pair having a 26 Å average separation distance, which is much longer than if the pair is confined within the covalent monomer. This implies that the charges are mobile within their respective segregated ZnTBTPP and PDI charge conduits.